TRANSFER TEKNOLOGI BIOFLOK PADA BUDIDAYA IKAN LELE : UPAYA PENINGKATAN PRODUKTIVITAS USAHA YANG RAMAH LINGKUNGAN - Taufik Budhi Pramono; Sri Marnani; Sukanto Sukanto (Fakultas Pertanian Universitas Yudharta Pasuruan, 2018)
The main problem caused by African catfish farmers is the input production inefficiency, namely the use of feed. The productivity and profit margins it produces are very low. Another problem with feed inefficiency that arises is the remaining feed at the bottom of the pond and can eventually cause toxins and even death in fish and production failure. One effort that needs to be done is to engineer biofloc technology. Biofloc technology in catfish farming is very important to be transferred to the fish farmers community. The purpose of this activity is to improve the knowledge, skills, and income of fish farmers. The method used is technology transfer, plot demonstration, and implementation of science and technology. The results show that the farming community is enthusiastic and trained in mastering biofloc technology. Its productivity reaches 568 Kg with high density and FCR reaches 0.7 and net profit reaches Rp. 2,850,000.